Physicochemical, particulate matter, temperature, and hydrological datasets collected from climate-threatened glacial river headwaters on the eastern slopes of the Canadian Rocky Mountains (2019-2021) - Jessica A Serbu; Vincent St.Louis; Craig Emmerton; Suzanne E Tank; Alison Criscitiello; Uldis Sillins; Maya P Bhatia; Maria Cavaco; Chloe Christenson; Colin Cooke; Hayley Drapeau; Sydney Enns; et al. (PANGAEA, 2023)
Here we provide a biogeochemical dataset containing 200+ parameters that we collected between 2019-2021 from the headwaters of three rivers (Sunwapta-Athabasca, North Saskatchewan, and Bow) which originate from the glacierized eastern slopes of the Canadian Rocky Mountains. River sampling sites were visited monthly in 2019 and 2020 during the open water season, beginning during snowmelt in late May/early June, through peak glacial melt in July/August, then during the receding flow period in September/October. Additional samples were collected twice in winter (December 2019, January 2021) during base flow, but only at sites where it was safe to do so. In general, at each river sampling site and time, we deployed a YSI EXO2 multiparameter sonde to obtain instantaneous measures of optical dissolved oxygen (ODO; % saturation and concentration), conductivity, turbidity, pH, and temperature. Sondes were calibrated at each sampling site for ODO, and prior to each sampling campaign for all other parameters. Using clean field sampling protocols, we also collected water samples for the analyses of total suspended solids (TSS); total dissolved solids (TDS); nutrients (total and dissolved phosphorus [TP, TDP] and nitrogen [TN, TDN], stable reactive phosphorus [SRP; 2020 only], ammonium [NH4+], nitrite and nitrate [NO2-+NO3-], and dissolved silica [Si]); major cations (Ca2+, K+, Mg2+, Na+) and anions (Cl-, SO42-); trace elements; water isotopes (δ2H-H2O, δ18O-H2O); particulate carbon (PC) and nitrogen (PN); dissolved inorganic and organic carbon (DIC, DOC); and the contaminants total and filtered mercury (THg, FHg), methyl- and filtered methyl-mercury (MeHg, FMeHg), and polycyclic aromatic hydrocarbons (PAHs; 2019 only). Integrated snow cores were collected with a stainless-steel corer once in March 2021 at peak snow accumulation. One fresh snow sample was also collected by skimming the surface of the snowpack after a major snowfall event the night prior. Rain samples were collected during a multi-day regional precipitation event in June 2023 by setting out wide-mouthed clean buckets lined with a clean plastic bags in on elevated surfaces in open areas to prevent ground-level splash back. Precipitation was originally collected for water isotope analyses and to estimate the potential influence of winter wet and dry deposition on chemical contributions to the rivers during snowmelt and rainfall. Water chemistry was also determined for a 10.2-meter ice core extracted from Snow Dome, the apex point of the Columbia Icefield, in April 2020 by the Canadian Ice Core Laboratory (CICL; University of Alberta). In January 2022 the CICL further collected surficial snow samples from longitudinal transects of the Athabasca and Saskatchewan glaciers that were subsequently analyzed for water isotopes. Mean daily river discharge (m^3/s) was directly quantified at two of our 14 sampling sites (SR2 and BR3) by hydrometric gauging stations maintained by Water Survey of Canada. To estimate daily discharge at the remaining 12 sampling sites, we used day-specific watershed area-discharge linear regression models derived from mean daily discharge measured at nine Albertan mountain river WSC hydrometric gauging stations. Given the importance of the headwaters of the Sunwapta-Athabasca, North Saskatchewan, and Bow rivers in establishing the initial dissolved and particulate biogeochemical loads of three major Canadian watersheds, and the projected timing of substantial glacier mass loss that indicates this region is presently on the brink of freshwater resource uncertainty, water quality research in these vulnerable headwaters is especially important. Thus, the purpose of this spatiotemporal dataset was to provide contemporary baseline reference for those investigating river headwaters stemming from the eastern slopes of the Canadian Rocky Mountains in the future, as well as increase our ability to predict the impact of climate change on the water quality of rivers originating in alpine glacierized regions. We also believe the possibilities for data exploration from this dataset are numerous and support further investigations to mine it for new biogeochemical studies.